Anomalies of the sigmoid colon during laparotomy exploration: a case report of a redundant colon in the sigmoid and transverse colon - Made Bagus Sastrapramaya Bharata; Made Dwi Yoga Bharata; I Gusti Ayu Agung Bella Jayaningrum (Intisari Sains Medis, 2021)
Introduction: The redundant colon is rare, often resulting in a late diagnosis because it is often asymptomatic and eventually leads to complications. The average person has a large intestine/colon 120-150 cm long in his abdominal cavity. The large intestine organ does not extend to the side but is tortuous to occupy the abdominal cavity. An abnormal condition can be found in the intestine length is beyond normal, known as “redundant colon”. The redundant colon may have additional loops or turns, which cause it to become longer. In people who experience the redundant colon, the process of removing feces in the body tends to be longer, so it often experiences constipation.Case description: In this case, A 40-year-old patient of female gender reportedly came to the BIMC Hospital and complaints of her abdominal pain, unable to defecate for 3 weeks ago, and did not improve with enemas. The patient had a history of total hysterectomy 13 years ago. The abdomen's physical examination is distended while inspected, there is no tenderness during palpation, and has normal auscultation. CT-Scan investigation found redundant transverse colon, low ileocecal junction location, and many intraluminal (colonic) stools, as well as plain abdominal images with obstruction of the large intestine. In patients, an exploratory laparotomy has been performed.Conclusion: Ileus obstruction was found due to momentum adhesion which tangled the sigmoid colon and was redundant in the transverse colon during the surgery. With proper management of this case, we hope this surgery can attain this case back to normal.